2015
DOI: 10.3109/15569527.2015.1074586
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and reliability of posterior sub-Tenon triamcinolone acetonide injection in branch retinal vein occlusion-related macular edema

Abstract: PSTA application is an effective and safe option in BRVO-related macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Nevertheless, we found that the effect of PSTA was no longer sustained after 3 months. Compatible with what was found by Kola et al, 34 PSTA exerted a short-term efficacy with significant visual improvement at 3 months, but disease recurred at 6 months, and the difference from baseline was no longer sustained ( p =0.846). The fading drug effect probably accounted for the observation.…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, we found that the effect of PSTA was no longer sustained after 3 months. Compatible with what was found by Kola et al, 34 PSTA exerted a short-term efficacy with significant visual improvement at 3 months, but disease recurred at 6 months, and the difference from baseline was no longer sustained ( p =0.846). The fading drug effect probably accounted for the observation.…”
Section: Discussionsupporting
confidence: 76%
“… Non-naive 30 56.3 (8.8) 30 Prospective, multi-centre 9 Wang et al a [ 53 ] Taiwan Aflibercept 2 mg Single injection then monthly PRN regimen. Naive 50 63.3 (6.9) 48 Retrospective, single-centre 12 Kola et al a [ 40 ] Turkey Triamcinolone Acetonide 40 mg (posterior sub-tenon) Single injection. Naive 41 63.5 (11) 36.6 6 Buyru Özkurt et al a [ 42 ] Turkey Subthreshold macular laser Single treatment then PRN regimen.…”
Section: Resultsmentioning
confidence: 99%
“…The most significant consequence, elevated intraocular pressure, affected 50% (two of four) patients, requiring one or more topical medications for reduction. This is higher than reported in prior studies of sub-tenon's triamcinolone monotherapy for macular edema secondary to retinal vein occlusions [7][8][9]. Due to the small sample size, however, it is unclear if the results would have been different if there was a larger patient sample.…”
Section: Discussionmentioning
confidence: 58%
“…Steroids reduce vascular permeability and also affect gene expression of inflammatory mediators [6], in addition to their ability to block VEGF. Sub-tenon's triamcinolone monotherapy has been shown to improve visual acuity at one month after administration for retinal vein occlusion, but has varying efficacy in regard to OCT thickness reduction [7][8][9]. These studies have shown rates of IOP elevation from 5%-29% of patients treated with posterior sub-tenon's triamcinolone monotherapy for macular edema secondary to retinal vein occlusion.…”
Section: Discussionmentioning
confidence: 99%